RISK MANAGEMENT IN PROJECTS OF PUBLIC-PRIVATE PARTNERSHIP - Victor Fursov; Natalia Lazareva (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the role ofpublic-private partnerships (PPP) as an effective tool for economic and social development at the regional and local levels, studied the mechanism of control and risk allocation of PPP for public and private partners, as well as the procedure of risk assessment as one of the stages of evaluating the effectiveness of projects of state private partnerships. The authors highlight the most important issues impeding the normal development of PPP in Russia, an attempt to develop step by step algorithm for estimating the risks of PPP allows you to manage them in the implementation of PPP projects with the aim of not only the return on investment, but also to receive dividends.